The Influence of Rare Plants Exploration in Taman Eden 100 Lumban Julu on Students' Science Process Skills - Manurung, N.; Tarigan, M. R. M.; Saputra, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to determine the significant effect of rare plant exploration activities in Taman Eden 100 Lumban Julu on students’ Science Process Skills (SPS) levels for deepening Biology learning material. The research method used was quasi-experimental with a significance level of α = 0.05. The data analysis technique used the group average effect test. The results showed that the result of the normality test on the pretest Lo Ltable was 0.1826 0.190 and on the posttest Lo Ltable was 0.1707 0.190, and the homogeneity test results obtained Fcount Ftable = 1.83 2.12. Hypothesis testing calculations obtained tcount ttable = 25.50 1.72. This study concludes that the level of students’ SPS by doing exploration has a significant influence. This can also be seen from the results of calculating the final increase (gain) score, where the gain value for each indicator is classified as medium and high. This shows that the science process skills possessed by students have increased.